ARABIC LANGUAGE LEARNING WITH THE "SEMI PROGRAMMED INDEPENDENT LEARNING" MODEL THE COVID-19 PANDEMIC AT MADRASAH TSANAWIYAH ALMAARIF 01 SINGASARI MALANG, INDONESIA - Rosyidi, Abdul Wahab; Machmudah, Umi (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
The sudden emergence of the Covid-19 pandemic caused madrasas and Arabic language teachers to implement distance learning, using a wide selection of the most effective approaches, strategies, methods, and techniques. In addition, the Internet is one of the means of choice for this. Madrasah Tsanawiah Al Maarif 01 Singasari in Malang, Indonesia is one of the schools that also implemented distance learning during the COVID-19 pandemic, but did not use the Internet. This study focuses on distance learning with a semi-independent learning model programmed on writing skills because most students live in Islamic boarding schools around the madrasa. With this type of descriptive research, the researchers want to explain the learning way of the learning model, concluding that it can help students practice in writing well and make it easier for teachers to check student worksheets, but not making the students becoming bored.